Classifying maternal deaths in Suriname using WHO ICD-MM: different interpretation by Physicians, National and International Maternal Death Review Committees - Lachmi R. Kodan; Kim J. C. Verschueren; Affette M. McCaw-Binns; Ray Tjon Kon Fat; Joyce L. Browne; Marcus J. Rijken; Kitty W. M. Bloemenkamp (BMC, 2021)
Abstract Plain English summary The World Health Organization (WHO) provides a framework (ICD-MM) to classify pregnancy-related deaths systematically, which enables global comparison among countries. We compared the classification of pregnancy-related deaths in Suriname by the attending physician and by the national maternal death review (MDR) committee and among the MDR committees of Suriname, Jamaica and the Netherlands. There were 89 possible pregnancy-related deaths in Suriname between 2010 and 2014. Nearly half (47%) were classified differently by the Surinamese MDR committee as compared to the classification of the attending physicians. All three MDR committees agreed that 18% (n = 16/89) of the cases were no maternal deaths. Out of the remaining 73 cases, there was disagreement regarding whether 15% (n = 11) were maternal deaths. The Surinamese and Jamaican MDR committees achieved greater consensus in classification than the Surinamese and the Netherlands MDR committees. The Netherlands MDR committee classified more deaths as unspecified than Surinamese and the Jamaican MDR committees. Underlying causes that achieved a high level of agreement among the three committees were abortive outcomes and obstetric hemorrhage, while little agreement was reported for unspecified and other direct causes. The issues encountered during maternal death classification using the ICD-MM guidelines included classification of suicide during early pregnancy; when to assume pregnancy without objective evidence; how to count maternal deaths occurring outside the country of residence; the relevance of direct or indirect cause attribution; and how to select the underlying cause when direct and indirect conditions or multiple comorbidities co-occur. Addressing these classification barriers in future revisions of the ICD-MM guidelines could enhance the feasibility of maternal death classification and facilitate global comparison. Background Insight into the underlying causes of pregnancy-related deaths is essential to develop policies to avert preventable deaths. The WHO International Classification of Diseases-Maternal Mortality (ICD-MM) guidelines provide a framework to standardize maternal death classifications and enable comparison in and among countries over time. However, despite the implementation of these guidelines, differences in classification remain. We evaluated consensus on maternal death classification using the ICD-MM guidelines. Methods The classification of pregnancy-related deaths in Suriname during 2010-2014 was compared in the country (between the attending physician and the national maternal death review (MDR) committee), and among the MDR committees from Suriname, Jamaica and the Netherlands. All reviewers applied the ICD-MM guidelines. The inter-rater reliability (Fleiss kappa [κ]) was used to measure agreement. Results Out of the 89 cases certified by attending physicians, 47% (n = 42) were classified differently by the Surinamese MDR committee. The three MDR committees agreed that 18% (n = 16/89) of these cases were no maternal deaths, and, therefore, excluded from further analyses. However, opinions differed whether 15% (n = 11) of the remaining 73 cases were maternal deaths. The MDR committees achieved moderate agreement classifying the deaths into type (direct, indirect and unspecified) (κ = 0.53) and underlying cause group (κ = 0.52). The Netherlands MDR committee classified more maternal deaths as unspecified (19%), than the Jamaican (7%) and Surinamese (4%) committees did. The mutual agreement between the Surinamese and Jamaican MDR committees (κ = 0.69 vs κ = 0.63) was better than between the Surinamese and the Netherlands MDR committees (κ = 0.48 vs κ = 0.49) for classification into type and underlying cause group, respectively. Agreement on the underlying cause category was excellent for abortive outcomes (κ = 0.85) and obstetric hemorrhage (κ = 0.74) and fair for unspecified (κ = 0.29) and other direct causes (κ = 0.32). Conclusions Maternal death classification differs in Suriname and among MDR committees from different countries, despite using the ICD-MM guidelines on similar cases. Specific challenges in applying these guidelines included attribution of underlying cause when comorbidities occurred, the inclusion of deaths from suicides, and maternal deaths that occurred outside the country of residence.